Reduced handgrip strength predicts poorer survival in chronic liver diseases: A large multicenter study in Japan - Nishikawa, Hiroki; Shiraki, Makoto; Hiramatsu, Akira; Hara, Nagisa; Moriya, Kyoji; Hino, Keisuke; Koike, Kazuhiko (Hepatology research, 2021)
Aim Sarcopenia has a high prevalence and can be an adverse predictor in patients with chronic liver diseases (CLDs). We sought to assess the prevalence of sarcopenia and its prognostic significance in patients with CLDs at multiple centers in Japan. Methods In this retrospective study, we collated the data of 1624 patients with CLDs (976 men). The diagnosis of sarcopenia was determined by the sarcopenia assessment criteria of the Japan Society of Hepatology. Predictors of mortality were identified using univariate and multivariate analyses. Results Muscle weakness and skeletal muscle loss occurred in 33.5% and 29.3% of all subjects, respectively, while sarcopenia occurred in 13.9% of all patients. Patients with sarcopenia had a poorer prognosis among all patients, patients with hepatocellular carcinoma (HCC), and those without HCC by log‐rank test. The multivariate Cox proportional hazards model identified female gender (hazard ratio [HR], 0.59; p = 0.03), alcoholic liver disease (HR, 4.25; p < 0.01), presence of HCC (HR, 6.77; p < 0.01), Child–Pugh classes A (HR, 1.42; p < 0.05), B (HR, 2.70; p < 0.01), and C (HR, 6.30; p < 0.01), and muscle weakness (HR, 2.24; p < 0.01) as significant adverse predictors. The cut‐off values of handgrip strength (HGS) for prognosis determined by maximally selected rank statistics were calculated as 27.8 kg for men and 18.8 kg for women. Conclusion Reduced HGS in patients with CLD was an independent adverse predictor of mortality, with cut‐off values of 27.8 kg for men and 18.8 kg for women.